Graphene-like dispersion and strong optical absorption in two-dimensional RP-type Sr3Ti2S7 perovskite - Liu, Hairui; Gao, Rui; Yang, Jien; Banthia, Rohan Dinesh; Yang, Feng; Wang, Tianxing; Upadhyaya, Hari M.; Jain, Sagar M. (American Chemical Society, 2023)
Two-dimensional (2D) Ruddlesden–Popper (RP) perovskite alloys have recently become attractive due to many desired physical properties originating from distinct van der Waals-type layered structures. In this work, a novel 2D RP-type Sr3Ti2S7 perovskite material design is proposed by using first-principles calculations. Our results reveal that the 2D Sr3Ti2S7 perovskite possesses dynamically stable structures, direct band structures with a band gap value of 0.86 eV, and a smaller effective mass (0.15/0.25 m0 for electron/hole) than MAPbI3 and phosphorene. More importantly, 2D Sr3Ti2S7 possesses wide optical spectra (from infrared-to ultraviolet-light region) and a higher absorption coefficient (105 cm–1) than MAPbI3, silicon, and MoS2 in the visible-light region. Interestingly, we also find that the ideal Dirac-like linear dispersion can appear near the Fermi level in the electronic band structures when compressive strain is applied. Especially, the Dirac-cone-like band structures can be realized when compressive strain is enhanced to −6%, indicating ultrahigh carrier mobility. These properties make the 2D Sr3Ti2S7 perovskite a promising candidate for future applications in solar cells and optoelectronic devices.
Keywords: Band structure; Electrical conductivity; Perovskites; Solar cells; Two dimensional materials